Entrepreneurship for dummies - Allen, Kathleen (New Jersey : John Wiley & Sons, Inc., 2023)
Entrepreneurship For Dummies is the essential guide to becoming your own boss and a successful entrepreneur. We make it simple to learn every step of the process. Identify an opportunity, learn your customers' needs, test your product, protect your intellectual property, secure funding, and get ready for that all-important launch. In classic Dummies style, this book is packed with practical information and useful advice, all in a fun and easy-to-follow format. Take fear out of the entrepreneurship equation and build the confidence you need to make your fantastic business idea take flight. Get up to date on the latest lingo, new ideas for raising money, and the latest ways to do business in the digital age. Understand the process of starting a business, from beginning to end. Complete the necessary planning and meet legal requirements, without the headache. Get expert tips and tricks on funding your idea and bringing your product or service to market. Build the foundation you need to keep your business thriving and growing. Entrepreneurship For Dummies supports you as you travel along the road to success.
PART 1: Getting started in entrepreneurship. Understanding entrepreneurship ; Entrepreneurship in the 21st century ; Preparing to seek opportunity ; Testing an opportunity before you leap -- PART 2: Testing the feasibility of your business concept. Understanding your industry ; What your customers can tell you ; Designing solutions for a new marketplace ; Protecting your products and services ; Putting together your founding team ; Getting solutions to customers: the supply chain ; Developing and testing your business model ; Assessing your initial financial needs -- PART 3: Designing a company. Preparing a business plan ; Finding money to start and grow your venture ; Starting with the right legal structure -- PART 4: Growing a company. Planning for growth ; Developing a marketing strategy ; Making and using money wisely: the financial plan ; Planning for things that go bump in the night -- PART 5: The part of tens. Ten reasons not to start a business ; Ten ways to spark your innovative spirit.
include index.